Science fictions. - Huangfu, Binghui; Pastor Roces, Marian; Earl Lu Gallery, LASALLE-SIA College of the Arts, Singapore (Singapore : Lasalle-Sia College of Arts, 2003)
Barker, Michele ; Ben-David, Zadok ; Bichaud, Jean-Luc ; Bureau d'Études ; Chua, Emily ; Cooper, Justine ; Constantino, Nicola ; Du, Wang ; Farrell, Rose ; Parkin, George ; Hiller, Susan ; Mengbo, Feng ; Shaomin, Shen ; et al.
Part of Singapore Arts Festival 2003, Lasalle-Sia College of Arts, Singapore, 6 June - 27 July 2003
kunstcatalogus